(Un)sustainability in a monetary union: Main factors in the Escudo Zone Monetary Union (1963-71) - Maria Eugénia Mata; Mário Jo\~ao Salvador Rold\~ao (Essays in Economic & Business History (EEBH), 2022)
An extensive literature praises economic integration and monetary unions as powerful means for economic convergence between, and the growth of, nations. Several potential factors have been flagged for successful economic convergence, such as labor availability and mobility and the role of initial levels of development (for positive business contagion effects). However, the relevance of this literature can be read differently in the context of a failed monetary union: the Escudo Zone Monetary Union (EZMU, 1963-1971), where policies key for sustainability were in place. This article investigates the operation of the EZMU and examines the important factors in its demise, thereby contributing to the discussion of (un)sustainability of convergence and economic integration.
Keywords: N10; N17; N20; N24; N27; 330; economic integration; Escudo Zone Monetary Union; monetary unions; Portugal; Portuguese colonial empire